Intervenciones de cuidado en enfermería a personas con abuso de sustancias psicoactivas por vía intravenosa. (2024)
This research was carried out with the objective of describing the interventions that Nursing implements for the care of people with psychoactive substance abuse intravenously, focusing on the treatment carried out by nursing in this type of patients. To carry out this objective, it was decided to carry out a review of the literature using the methodology proposed by Whittemore and Knafl.